Microstructure and tribological behaviour of Al2O3 particle-reinforced aluminum alloy composite: A comparative study - (:unkn) unknown (Scientific Bulgarian Communications, 2014)
This paper presents the tribological behaviour of aluminum 2124 alloy reinforced with 10 wt.% Al2O3 particles, produced by powder metallurgy (PM) method. A comparison is made between MMCs and its coated MMCs generated by anodic oxidation method under the similar condition. Scanning electron microscope (SEM) observation of the microstructure shows that dispersion of Al2O3 particles within Al2124 alloy is uniform for the larger particle-reinforced composite, but increased amount of agglomerations among particles is observed for the smaller particle-reinforced composite. Hardnesses of both MMCs increased with increasing the particle size and coating process, but the coating was more effective for the alloy than that of particle-reinforced composite. The experimental results exhibited that the lower wear rate is obtained for the coated composite, the wear rate increased linearly with increasing loads and decreased with increasing particle sizes. Moreover, SEM examination of worn surfaces showed that adhesion, abrasion, and delamination of mechanically mixed layer were dominant for the matrix and its composites under high loads. Craters wear with a slight abrasion and delamination was effective for the lower size of the coated composite, but abrasive grooves and delamination were found to be responsible for material removal of the coated larger particle composite.
Keywords: Al2124; Coating; Hardness; Powder metallurgy; Wear